PENGARUH JENIS PENGENCER SEMEN TERHADAP MOTILITAS, ABNORMALITAS DAN DAYA TAHAN HIDUP SPERMATOZOA AYAM BURAS PADA PENYIMPANAN SUHU 5 oC - Ridwan Ridwan (Universitas Tadulako, 2008)
The aim of the experiment was to study the influence of semen diluter types on the mortality, abnormality and live endurance of local chicken spermatozoa stored at 50C. The diluter treatments applied were as followed: i) Physiological NaCl (P1), ii) Lactate ringer solution (P2), iii) Dextrose ringer solution. Analysis of variance results showed that the diluters significantly affected (P<0.01) all parameters determined. The spermatozoa mortality were 81,79% for P1, 76.57 % for P2, and 84.32% for P3. The spermatozoa abnormalities were 4.08% for P1, 5.2% for P2, and 3.4% for P3. The spermatozoa live endurance for 4 days were73.28% for P1, 68.98% for P2 and 77.72% for P3. According to the Least Significant Test, the dextrose ringer solution was found to be the best diluter